Qualitative Investigation of Adaptive Divorce: Case Study of Talesh Males During 2014 - sorayya pournasiri; Behrouz Roustakhiz; daryoush boustani (توسعه اجتماعی)
This study aims to investigate the contexts, conditions, process and consequences of the adaptive divorce in Talesh. 18 males who had adaptively divorced participated at this study. Participants and concepts were selected by one of the strategies of purposive sampling, maximum variety and theoretical sampling. Data were analyzed by using qualitative methodology of grounded theory. The in-depth interview was the technique of collecting data. Finally, 12 categories and a core category were extracted during coding process which are: perceived crudity for marriage; precipitant familiarity; interfere and importance of significant others; disagreement of family; status differences; infidelity of spouse; ongoing contentions; agreement for separation; Bargaining and agreement on dowry; pain of separation; satisfaction of remarriage; believe in better life after divorce. Finally, the core category extracted as” superficiality, infidelity and difference as the passage of adaptive divorce”.